2018
DOI: 10.26637/mjm0602/0021
|View full text |Cite
|
Sign up to set email alerts
|

Effect of space and temperature dependent internal heat generation/absorption on Casson fluid flow in the presence of an inclined magnetic field

Abstract: The present study focuses on the inclined magnetic field effect on Casson fluid flow over a stretching sheet with non-uniform heat source/sink. The velocity slip boundary conditions are considered. A similarity transformation of governing equation is used to reduce into a non-dimensional form. The flow and thermal equations are derived and solved analytically by using confluent hypergeometric function and numerically by using shooting iteration technique together with Runge-Kutta fourth order. Results for vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…It is found that, as the Casson parameter increases, the wall skin friction decreases; an analytical solution for flow of Casson fluid along a stretching surface with considering of viscous dissipation and thermal radiation effects [22]. It is observed that the thermal radiation effect on the temperature is very large in the case of injection than the suction case; the influence of an inclined magnetic field with the velocity slip boundary conditions on the flow of Casson fluid along a stretching sheet [23]. The results refer to the momentum boundary layer thickness decreases with increasing magnetic parameter and angle parameter, slip parameter and Casson parameter; the flow of an unsteady MHD mixed convection of Casson fluid in the recession area of a headily rotating sphere [24]; entropy generation analysis for the unsteady problem of magnetohydrodynamic (MHD) convection flow and heat transfer of non-Newtonian Casson fluid along stretching sheet with magnetic field effect [25].…”
Section: Introductionmentioning
confidence: 97%
“…It is found that, as the Casson parameter increases, the wall skin friction decreases; an analytical solution for flow of Casson fluid along a stretching surface with considering of viscous dissipation and thermal radiation effects [22]. It is observed that the thermal radiation effect on the temperature is very large in the case of injection than the suction case; the influence of an inclined magnetic field with the velocity slip boundary conditions on the flow of Casson fluid along a stretching sheet [23]. The results refer to the momentum boundary layer thickness decreases with increasing magnetic parameter and angle parameter, slip parameter and Casson parameter; the flow of an unsteady MHD mixed convection of Casson fluid in the recession area of a headily rotating sphere [24]; entropy generation analysis for the unsteady problem of magnetohydrodynamic (MHD) convection flow and heat transfer of non-Newtonian Casson fluid along stretching sheet with magnetic field effect [25].…”
Section: Introductionmentioning
confidence: 97%